The sisters of the Muslim Brotherhood: Islamic activism for better or for worse - Elserafy, Amira (AUC Knowledge Fountain, 2014)
This study is meant to tell the story of the Muslim Brotherhood Sisters (Al-Akhawat Al-Muslimat) in urban Cairo, Egypt. It mainly attempts to answer two questions: (1) what motivates the Sisters’ Islamic activism within the Brotherhood and within the Egyptian society at large despite its huge risks? (2) how do they (re)construct, contest and relate to the gender ideology of the Muslim Brotherhood? Relying on ethnographic fieldwork, this study explores the ways through which the Sisters of the Muslim Brotherhood conceptualize their engagement in Islamist politics amid the crackdown of 2013. Through examining the Muslim Brotherhood’s contexts, contention repertoires and cultural framing, this project discusses how the movement seeks to recruit and engage young university educated and career accomplished women who set out to change the political and the societal scene. It also argues that the gender ideology of the Muslim Brotherhood is not static, nor is it a discourse in vacuum, but rather a reflection of wider societal views on gender roles and gender dynamics.